1978
DOI: 10.1063/1.325360
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in the Co/Si thin-film system. II. Diffusion-marker experiments

Abstract: The Kirkendall effect in thin-film Co/Si couples is investigated by He backscattering using diffusion markers. The couples contain the compounds Co2Si and CoSi. The markers used are Xe implanted into Si, C, or Co2Si and a discontinuous W film between Si and Co. In the case of Xe implantation into Co, the experiments can be explained by dragging of Xe bubbles by the moving Co/Co2Si phase boundary. Xe implanted into Si is located at the Si/CoSi interface after the reaction and W is found at the Co/Co2Si interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…The high-resolution image taken around the interface ͑shown on the right͒ further reveals that small islands ͑ϳ5 nm in size͒ of CoGe are barely connected with each other just underneath the interface between Co and Ge, the appearance of which suggests that Co atoms have probably diffused into the Ge substrate and subsequently reacted with Ge to form the CoGe phase, similarly to the well-known initial solid-state reaction of Co with Si. 15 The high-resolution image also shows the existence of a discrete, bright layer between the unreacted Co and CoGe, which is believed to be the segregation of oxygen swept out of the growing germanide. A similar observation was also reported in the Co/Si system due to the initial presence of oxygen at the Co/Si interface and within the Co film, and the low reduction capability of the Co film.…”
Section: Resultsmentioning
confidence: 96%
“…The high-resolution image taken around the interface ͑shown on the right͒ further reveals that small islands ͑ϳ5 nm in size͒ of CoGe are barely connected with each other just underneath the interface between Co and Ge, the appearance of which suggests that Co atoms have probably diffused into the Ge substrate and subsequently reacted with Ge to form the CoGe phase, similarly to the well-known initial solid-state reaction of Co with Si. 15 The high-resolution image also shows the existence of a discrete, bright layer between the unreacted Co and CoGe, which is believed to be the segregation of oxygen swept out of the growing germanide. A similar observation was also reported in the Co/Si system due to the initial presence of oxygen at the Co/Si interface and within the Co film, and the low reduction capability of the Co film.…”
Section: Resultsmentioning
confidence: 96%
“…25 Previous studies showed that the growth of CoSi is diffusion limited. 26,27 Furthermore, marker experiments showed that Si is the dominant diffusing species. 28 For the diffusionlimited case, the growth of CoSi is governed principally by the diffusion of dominant diffusing species.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Co 2 Si/Si interface will move into Si by Co atom motion since Co is the primary diffusing species [18].…”
Section: Discussionmentioning
confidence: 99%